The Influence of Grammatical Sensitivity and Learning Style on Writing Ability - Moh Hanafi; Ayu Septiana (STKIP PGRI Trenggalek, 2021)
This study was conducted to see the relationship of grammatical sensitivity and learning style on writing ability. A correlational research design was chosen as the design of this research with three variables to be tested, that is, grammatical sensitivity, learning style and writing ability. The data analysis showed that the mean score of grammatical sensitivity was 18.81 which is on medium level of grammatical sensitivity. Moreover, the students were mostly visual learning style students. Meanwhile, the writing test showed that they had good writing ability with mean score of the class 81.57. Based on the result of the data analysis of regression, it was found that 1) Partially, there is significant correlation between the students’ grammatical sensitivity and writing ability; 2) Partially, there is no significant correlation between students’ learning style and writing ability; 3) Simultaneously, there is a significant influence of grammatical sensitivity and learning style on students’ writing ability.